Impact of Minimum Wages, Education, Foreign Direct Investment, and Exports Labour Absorption in the Manufacturing Sector in Eight ASEAN Countries - Zulia Adena; Septriani Septriani (Academic Bright Collaboration, 2026)
Purpose – This study examines the effects of minimum wages, education, foreign direct investment (FDI), and exports on manufacturing labour absorption in eight ASEAN countries from 2014 to 2023, addressing the persistence of jobless industrial growth. Methods – A quantitative explanatory design was applied to balanced panel data. First-difference panel regression was used to address non-stationarity, with the Random Effects Model selected through the Chow, Hausman, and Lagrange Multiplier tests. Data were obtained from ASEANstats, the World Bank, ILOSTAT, UNDP, Country Economy, and other official sources. Findings – Minimum wages and exports have positive and significant effects on labour absorption, while FDI has a significant negative effect. Education has a positive but insignificant effect, indicating that employment is shaped more by industrial structure, export performance, and investment orientation than by formal educational attainment. The results suggest efficiency-wage effects, capital-intensive FDI, persistent skill mismatches, and the employment-enhancing role of exports. Research Implications – ASEAN countries should strengthen export competitiveness, attract employment-oriented investment, align workforce skills with industrial demand, and implement gradual productivity-based minimum wage policies. Expanding formal manufacturing employment may also broaden the tax base and strengthen fiscal capacity. Originality – This study provides cross-country evidence on the determinants of manufacturing labour absorption in ASEAN and links employment outcomes to economic formalization, fiscal capacity, and sustainable governance. It highlights a pattern in which industrial growth and FDI do not necessarily generate proportional employment, whereas minimum wages and exports support labour absorption.